The effect of exercise on left ventricular global longitudinal strain: a systematic review and meta-analysis. (4th February 2022) - Murray, J; Bennett, H; Bezak, E; Perry, R; Boyle, T
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Cancer Research Institute, Allied Health and Human Performance, University of South Australia Background/Introduction Left ventricular global longitudinal strain (LVGLS) can detect early myocardial changes prior to clinical abnormalities arising, and is a strong prognostic indicator of future cardiovascular (CV) dysfunction and mortality. It is well established that exercise improves CV function and reduces risk of CV disease. However, the impact of exercise on LVGLS is currently unclear. If LVGLS increases in response to habitual exercise, it could offer a sensitive measure that can determine the effectiveness of an exercise regime on CV health. Purpose: The aim of this systematic review and meta-analysis was to determine whether exercise impacts LVGLS across a range of healthy and diseased populations. Methods: Four databases (Medline, Scopus, eMbase, SPORTDiscus) were searched in November 2020. Included studies assessed LVGLS before and after an exercise intervention (minimum 2 weeks) in adults aged 18 years and over, and were published in English from 2000 onwards. Random-effects meta-analyses were performed at a study level using Stata (v16.1) to calculate summary standardized mean differences (SMD) and 95% confidence intervals (CI). 39 studies met selection criteria, with 35 included in meta-analyses (1765 participants). Primary meta-analyses included only studies that compared outcomes between one or more intervention arms to a standard (non-exercising) control arm (RCT's, N-RCT's, randomised crossover). Secondary analyses included data from studies with intervention arms only (single group pre-post studies, intervention group from RCT's, N-RCT's, randomised crossover). Results: Primary: In populations with CV disease, a moderate effect of exercise was observed compared to non-exercising controls (SMD = 0.59; 95% CI, 0.16-1.02; p = 0.01 – figure 1a). No significant effect of exercise was observed for CV risk (SMD = 0.07; 95% CI, -0.15-0.29; p = 0.56 – figure 1b) and healthy (SMD = -0.20; 95% CI, -0.73-0.33; p = 0.45) populations compared to non-exercising controls. Secondary: In secondary meta-analyses, significant effects of exercise were observed in CV disease (SMD = 0.26; 95% CI, 0.07-0.46; p = 0.01), CV risk (SMD = 0.54; 95% CI, 0.15-0.93; p = 0.01), chronic kidney disease (SMD = 0.65; 95% CI, 0.03-1.28; p = 0.04) and athletic (SMD = 0.30; 95% CI, 0.20-0.41; p= <0.001) populations. Conclusion(s) Increases in LVGLS observed in populations with CV disease may assist the prevention of secondary CV events. Secondary findings may support the use of exercise across a range of populations to increase LVGLS and enhance CV function. Future research must address the methodological limitations that currently exist, including improving upon study designs and reporting of individual data.